Fever, 1793 - Anderson, Laurie Halse, 1961- (Simon & Schuster Books for Young Readers, 2000)
In 1793 Philadelphia, sixteen-year-old Matilda Cook, separated from her sick mother, learns about perseverance and self-reliance when she is forced to cope with the horrors of a yellow fever epidemic.